A critical review on wireless power transfer systems using metamaterials - Thanh Son, Pham; Bui Xuan Khuyen; Bui Son Tung; Le Thi Hong Hiep; Vu Dinh Lam (Vietnam Journal of Science and Technology, 2022)
Recently, wireless power transfer (WPT) has been a topic of interest due to its attractive applications in modern life. Starting from Tesla’s idea about a century ago, WPT has developed tremendously and appeared in many of the most modern electronic devices. However, some WPT systems still have limitations such as short transmission distance, low transfer efficiency, and electromagnetic leakage. Magnetic metamaterial (MM) is a potential candidate that can overcome the above disadvantages of WPT. This paper is intended to present an overview of recent advances and research progress on WPT systems. Three classes of WPT consisting of short-range, mid-range, and long-range, will be analyzed in detail both in terms of fundamentals and applications. Especially, MM configurations can be used to enhance the near-field WPT efficiency and reduce the leakage of electromagnetic field will also be evaluated. This article is expected to provide a comprehensive review of the mechanism and applications as well as the future development of metamaterial-based WPT systems.